Examining the prospects of multilateralism security in Asia Pacific : Asean Regional Forum. - Foo, Chee Oon. (2008)
The end of Cold War witnessed the emergence of what may be called Asia Pacific multilateralism which can make important contributions to the maintenance of regional peace and stability. The quest for a multilateral security framework in Asia Pacific led to the creation of ASEAN Regional Forum (ARF) in 1994. Therefore, the paper begins with a conceptual analysis of multilateralism and it tenets of co-operative security that ARF tries to adapt in its effort to construct a new security architecture in the region. The paper also traces the past multilateral security experiences and the evolution of ARF. This paper attempts to examining two sides of a coin on the prospects of ARF by looking at its limited progress and constraints. It argues that the behaviour of China is a key determinant of ARF's success and the US-China-Japan relationship has a great impact on the fate of ARF.